Create Amazing - Graves, Greg (Ascent Audio, 2021)
There are more than 10,000,000 employee owners in America today. The results of employees owning a piece of the pie has been proven throughout American history, even before ESOPs became IRS law in 1974. Employees with even a small capital interest in their firms' successes are more likely to stay, have greater loyalty and pride, are willing to work hard, and make more suggestions for improvement. Economic injustice caused by wealth disparity is quickly becoming the hottest debated topic in America. Employee ownership is not the only answer for economic justice but it can be a critical puzzle piece for tens of millions of Americans where the current inherent disadvantage of circumstance stands in their way. Create Amazing demonstrates how ownership can provide the ultimate competitive advantage to a growing company-and the nation. Greg Graves, who operated one of the most successful ESOPs in American history, shares: the history of employee ownership in America and the principles of its purpose; why employee ownership is a viable solution fiscally and futuristically; what an ESOP is, what it does, and what's happening in Washington DC to promote this model; how ESOPs work, and how they're structured legally, fiduciarily, and financially; and the impact of ESOPs on America and on employee owners personally.